High strung : Bjorn Borg, John McEnroe, and the untold story of tennis's fiercest rivalry - Tignor, Stephen (New York : Harper, 2011)
c
Keywords: Borg, Bjorn, -- 1956-; McEnroe, John, -- 1959-; Tennis players -- United States -- Biography; Tennis players -- Sweden -- Biography; Sports rivalries